Distribution and Composition of Thiotrophic Mats in the Hypoxic Zone of the Black Sea (150–170 m Water Depth, Crimea Margin) - Jessen, Gerdhard L.; Lichtschlag, Anna; Struck, Ulrich; Boetius, Antje (Frontiers in Microbiology, 2016)
At the Black Sea chemocline, oxygen- and sulfide-rich waters meet and form a niche for thiotrophic pelagic bacteria. Here we investigated an area of the Northwestern Black Sea off Crimea close to the shelf break, where the chemocline reaches the seafloor at around 15-170 m water depth, to assess whether thiotrophic bacteria are favored in this zone. Seafloor video transects were carried out with the submersible JAGO covering 20 km2 on the region between 110 - 200 m depth. Around the chemocline we observed irregular seafloor depressions, covered with whitish mats of large filamentous bacteria. These comprised 25 to 55% of the seafloor, forming a belt of 3 km width around the chemocline. Cores from the mats obtained with JAGO showed higher accumulations of organic matter under the mats compared to mat-free sediments. The mat-forming bacteria were related to Beggiatoa-like large filamentous sulfur bacteria based on 16S rRNA sequences from the mat, and visual characteristics. The microbial community under the mats was significantly different from the surrounding sediments and enriched with taxa affiliated with polymer degrading, fermenting and sulfate reducing microorganisms. Under the mats, higher organic matter accumulation, as well as higher remineralization and radiotracer-based sulfate reduction rates were measured compared to outside the mat. Mat-covered and mat-free sediments showed similar degradability of the bulk organic matter pool, suggesting that the higher sulfide fluxes and subsequent development of the thiotrophic mats in the patches are consequences of the accumulation of organic matter rather than its qualitative composition. Our observations suggest that the key factors for the distribution of thiotrophic mat-forming communities near to the Crimean shelf break are hypoxic conditions that (1) repress grazers, (2) enhance the accumulation and degradation of labile organic matter by sulfate-reducers, and (3) favor thiotrophic filamentous bacteria which are adapted to exploit steep gradients in oxygen and sulfide availability; in addition to a specific seafloor topography which may relate to internal waves at the shelf break